Genotype-phenotype correlation in a family with Arg135Leu rhodopsin retinitis pigmentosa. Issue 12 (17th November 2004) - Oh, K T; Oh, D M; Weleber, R G; Stone, E M; Parikh, A; White, J; DeBoer-Shields, K A; Streb, L; Vallar, C
Abstract : Aim: To describe the clinical characteristics and disease course of a large family with retinitis pigmentosa (RP) from an Arg135Leu change in rhodopsin. Methods: 29 patients in this family were evaluated. Goldmann visual fields were performed on 14 affected individuals, Ganzfeld electroretinography (ERG) on eight individuals (11–56 years), and blood samples collected on 10 individuals (11–58 years). Patient visual field data were compared with previously reported patients with different rhodopsin mutations using linear regression. Results: An Arg135Leu mutation was identified in rhodopsin. Distinct stages of clinical evolution were identified for this family ranging from normal, white dots, classic bone spicules and, finally, ending with extensive retinal pigment epithelium (RPE) atrophy. 9/16 patients over the age of 20 years also demonstrated marked macular atrophy. All patients who underwent full field ERG testing demonstrated non-recordable ERGs. The overall regression model comparing solid angles of visual fields from patients with rhodopsin mutations (Pro23His, Pro347Ala, Arg135Leu) shows significant effects for age (p = 0.0005), mutation (p = 0.0014), and interaction between age and mutation (p = 0.018) with an R 2 of 0.407. Conclusions: An Arg135Leu change in rhodopsin results in a severe form of RP that evolves through various fundus appearances that include white dots early in life and classic appearing RP later. This transmembrane change in rhodopsin proves to be more severe than in a family with an intradiscal change and a family with a cytoplasmic change.